A modern nerd's guide to steampunk - Horning, Nicole (Geek out!, 2020)
". . . The world of steampunk combines the look of the steam-powered 19th century with the technology of the present or ideas about the future. This . . . way to bring history and STEM topics together is popular with people of all ages, and this . . . guide gives young readers . . . information about steampunk--from its roots to ways to dress like a steampunk character . . . Photographs, detailed graphic organizers, and informative sidebars enhance this . . . reading experience"--Provided by publisher.